Digital diaspora: Exploring the social networking dynamics of international students in Chandigarh, India - Dhiman, Pankaj; Paliktzoglou, Vasileios (Journal of Interdisciplinary Studies in Education, 2024)
In this paper, we examined the relationship between social networking sites (SNSs) and the coping strategies international students adopt amidst cultural shocks in India, particularly in the vibrant locale of Chandigarh. The study scrutinizes pivotal factors that influence international students’ SNS use and creates and validates an instrument that measures this relationship. Grounded in the uses and gratifications theory (UGT), this research introduces an instrument—the Social Capital Assessment Scale and Inventory (SCASI), which was developed via exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The research concludes that SNSs play a pivotal role in the globalization of information, encompassing education, knowledge dissemination, interactivity, and cultural exchange in geographically diverse countries such as India.